Strategi Digital Marketing Melalui Tiktok Dalam Membangun Brand Trust Generasi Z - Rahasdita Reo Hansdoko; Fitria Ayuningtyas; Nurannafi Farni Syam Maella; Didik Sugeng Widiarto (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This study aims to analyze digital marketing strategies through the TikTok platform in building brand trust among Generation Z. TikTok is highly relevant due to its large Gen Z user base and interactive features that support viral content distribution. Using a descriptive qualitative approach, this research analyzes digital content from the MS Glow brand during the period of January to June 2025. The findings indicate that strategies such as storytelling, collaboration with micro-influencers, user-generated content, and social value campaigns are effective in enhancing brand trust. This study offers practical insights for marketers in designing relevant digital communication strategies for Gen Z.